CURRENT IDEAS ABOUT THE ROLE OF THE IMMUNE SYSTEM IN THE DEVELOPMENT OF OVARIAN DYSFUNCTION IN WOMEN OF REPRODUCTIVE AGE (LITERATURE REVIEW) - Азизова З.Ш.; Мусаходжаева Д.А.; Мухамедов Р.С.; Рузимуродов Н.Ф.; Жанговаров А.Ж.; Рамзиддинов Ж.Ж. (Modern American Journals, 2025)
Topicality. Ovarian dysfunction is one of the leading causes of female infertility, manifesting itself in the form of anovulation, premature ovarian exhaustion (POI), polycystic ovary syndrome (PCOS), and reduced response to gonadotropic stimulation. Modern research increasingly indicates the involvement of the immune system in the pathogenesis of these conditions, which requires systematic analysis and generalization of data.
Keywords: ovarian dysfunction, immune system, cytokines, autoantibodies, polycystic ovary syndrome, premature ovarian failure, FOXP3, HLA-G.